Pemanfaatan Limbah Cangkang Kerang Darah sebagai Adsorben untuk Adsorpsi Zat Warna Methyl Orange - Cindy Aprilianti; Romy Dwipa Yamesa Away (MASALIQ, 2025)
Methyl orange is a toxic, carcinogenic, and mutagenic dye commonly found in textile industry wastewater, posing a serious threat to the environment. This study aims to determine the optimal conditions for the adsorption of methyl orange using a natural adsorbent derived from blood clam (Anadara granosa) shell waste, which remains underutilized despite being abundant and rich in calcium oxide (CaO). The methodology consisted of three main stages: adsorbent preparation, adsorption process, and concentration analysis using UV-Vis spectrophotometry. The variables investigated included adsorbent mass (7, 9, 11, and 13 grams), contact time (20, 40, 60, and 100 minutes), and solution pH (1, 3, 5, and 7). In addition, CaO content was analyzed using X-Ray Fluorescence (XRF) after the calcination process. The results indicated that the optimal adsorption condition was achieved with 11 grams of adsorbent, 60 minutes of contact time, and a solution pH of 1, resulting in an adsorption efficiency of 85.35%. XRF analysis revealed that the blood clam shell contained 97.704% CaO, which significantly contributed to its adsorption performance. These findings demonstrate that blood clam shell waste has strong potential as a low-cost, efficient, and environmentally friendly alternative adsorbent for treating textile dye wastewater.